PKM SISTEM INFORMASI PARIWISATA BERBASIS WEBSIG PADA WISATA ALAM KECAMATAN SIBOLANGIT, KAB. DELI SERDANG, SUMUT - Ekatri Ayuningsih; Zubaidah Hanum; Yeni Rachmawati; Rizaldy Khair; Ramadani (Cattleya Darmaya Fortuna, 2022)
Sibolangit District is one of the sub-districts located in the highlands area which is blessed with beautiful tourism potential and attracts tourists, both foreign tourists and domestic tourists. The use of the website as a medium to promote tourism in the area was very much needed. With the existence of a WebGIS-based tourism information system, it was expected to be able to increase the number of tourists visiting the location. The Web-based tourism information system application method in Sibolangit sub-district aimed to abtain a mapping of tourist sites in the form of a geographic information system. This was not without reason, because tourists needed location information, entrance fees, facilities and the natural beauty on offer. Mapping locations and providing information related to tourism can provide a high effort for easy access to spatial data and detailed information needed. The main target in implementing community service activities was to assist tourism managers to increase the number of local and foreign tourists through the use of WebGIS.